Estudo da implementação do ensino remoto emergencial em cursos de graduação em uma instituição pública federal : desafios e implicações pedagógicas para a educação superior presencial - Ernane Henrique de Oliveira (2023)
The objective of this research was to investigate the implementation of Emergence Remote Teaching in the undergraduate courses of a Higher Education Federal Public Institution, identifying actions implemented, challenges and learnings built along this process. In that sense, we set focus on the following problem: how Emergence Remote Teaching was implanted in the undergraduate courses of a Higher Education federal public institution and which repercussions were identified in the field of the teacher-student relationship, in the teaching e evaluation practices? From this problem arouse other questionings, namely: Which planning and evaluation actions were organized for the implantation of Emergence Remote Teaching? Teachers and students were consulted in this process? Which challenges were identified? Which relevant learning and practices were built along Emergence Remote Teaching? What is the level of satisfaction of the teachers and students about the implemented Emergence Remote Teaching? Which lessons pandemics has brought for the processes of teaching and evaluation at the university, in view of the post-pandemic period? The methodology of the research involved literature review, documentary research and exploratory study of qualitative nature. The empirical research used as procedures for data gathering: interview with teachers, students and members of commission of monitoring and evaluation. The results evinced that were identified different challenges for the implementation of Emergence Remote Teaching, among which: lack of equipment and internet in order to access the classes in the part of the students, lack of a proper place for attending the classes and for study, gaps in the teachers’ training for the pedagogical use of digital platforms, difficulties for the elaboration of evaluative activities proper to this teaching format, among others.